-5(x+1)+3x=6-(4x-3) solve for x
1 answer:
Answer: x = -3
Step-by-step explanation:Step by step solution :
Step 1 :
Pulling out like terms :
1.1 Pull out like factors :
-x - 3 = -1 • (x + 3)
Equation at the end of step 1 :
Step 2 :
Solving a Single Variable Equation :
2.1 Solve : -x-3 = 0
Add 3 to both sides of the equation :
-x = 3
Multiply both sides of the equation by (-1) : x = -3
One solution was found :
x = -3
You might be interested in
X varies directly as y
x = ky
3 = 2k
k =
![\frac{3}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B2%7D%20)
when x =9
9 =
![\frac{3}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B2%7D%20)
y
![\frac{18}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B18%7D%7B3%7D%20)
= y
∴y = 6
please mark as brainliest
Answer:
9/40
Step-by-step explanation:
3/5 * 3/8 = 9/40
Answer:
5
Step-by-step explanation:
(4+11)/3 = 15/3 = 5
-9x7 mutiplies to be -63, and add up to be -2.
The answer is 9 because you solve it from left to right and 3x5 equals 15, 15 subtracted by 6 equals 9